Underrepresented Students and the Transition to Postsecondary Education: Comparing Two Toronto Cohorts - Robson, Karen; Anisef, Paul; Brown, Robert S.; George, Rhonda (Canadian Journal of Higher Education, 2018)
Using data from two cohorts of Grade 12 students in Toronto, we examined whether the transition to post-secondary education changed between 2006 and 2011, particularly for under-represented groups. We used multilevel, multinomial logistic regressions to examine how the intersections of race and sex affect post-secondary transitions in the two cohorts. Our findings revealed that Black, Latino, and Southeast Asian students were less prepared for post-secondary education than White students. Students in these groups had lower than average GPAs, higher identification of special education needs, or lower likelihoods of taking academic-stream courses. These differences remained fairly stable between 2006 and 2011. We did, however, find that Black students were more likely than White students to confirm a place in university in 2011—a significant difference. In contrast, Southeast Asian students experienced a decline in university transition but an increase in college confirmation. We also found that race and sex were important intersections for university confirmations in the case of Blacks and for college confirmations in the case of Southeast Asians. We contextualize our findings within the policy climate of Ontario in the years spanning our two cohorts.